Efficiency of using timer signal constructions in the city telephone network channels - Рябуха, Олександр Миколайович (Eastern-European Journal of Enterprise Technologies, 2014)
New, more efficient transmission methods, providing a necessary transmission quality and the transmission of more information in a given time interval are proposed. Use of time-coding in transmission systems reduces information delivery time by two times compared with BDC (bit-digital coding). It is experimentally shown that although power distance in timer signal constructions is defined by the area, much smaller relative to the bit-digital code, the probabilities of false acceptance of CW (code word) are not significantly different, and sometimes may be smaller than the bit-digital code. The results of statistical measurements on these channels are given, and probabilistic characteristics of systems when using timer signal constructions for the information transmission through the city telephone network channels are calculated in the paper.